Economic determinants of optical fiber share in total broadband connections in OECD countries - Tatcha Sudtasan (International Telecommunications Society (ITS), 2015)
This study realizes the benefits of optical fiber broadband as an economic stimulation thus it analyzes the determinants of optical fiber share in total broadband connections in OECD countries with the focus on the demand-driven factors and the government roles as the stimulator, the regulator and the investor in the optical fiber sector. It constructs a panel data set using the data during 2012-2014 and estimates the fixed and random effects model with the judgment of the best model by Hausman test. The results reveals that the share of optical fiber behaves well according to the demand theory on the own-price and cross-price effects. Education is a must to support the growth of optical fiber. The government roles differ in their effects, i.e. the role of stimulator and the regulation of local loop unbundling enhance the growth of optical fiber deployment and adoption while the role as the investor negatively impacts the share. Moreover, the study also examines the effects of government roles of regulation regarding to intra-platform competition on the unit price of optical fiber. It discovers that initially the larger number of competitors drives the unit price down by their competition, but later after the establishment of giant incumbent firms in the market and gain sufficient market power and the control over prices such that the number of new comers cannot affect the growing trend of the unit price of the optical fiber broadband.
Keywords: L96; L52; D12; 330; Fixed broadband penetration; fixed broadband share; optical fiber internet; optical fiber share; consumer behavior